1988
DOI: 10.1084/jem.167.3.1211
|View full text |Cite
|
Sign up to set email alerts
|

Cachectin/tumor necrosis factor induces cachexia, anemia, and inflammation.

Abstract: Severe weight loss and debilitative wasting of lean body mass frequently complicate the treatment of patients suffering from malignancy or chronic infection. Termed cachexia, this syndrome of anorexia, anemia, and weakness further increases cancer mortality; some data indicate that as many as 30% of cancer patients die from cachexia, rather than tumor burden (1-3). The severity of cachexia may be unrelated to tumor size or parasite load, and profound wasting has been observed in patients with tumor burdens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
275
0
20

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(307 citation statements)
references
References 48 publications
12
275
0
20
Order By: Relevance
“…Several studies have revealed possible ways in which excessive TNF production could contribute to this phenomenon (Tracey et al, 1988;Lindemann et al, 1989;Denz et al, 1993;. Importantly, all these adverse conditions may result in a poor performance status of the host and may influence the patient's ability to tolerate therapy and, as a consequence, result in a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed possible ways in which excessive TNF production could contribute to this phenomenon (Tracey et al, 1988;Lindemann et al, 1989;Denz et al, 1993;. Importantly, all these adverse conditions may result in a poor performance status of the host and may influence the patient's ability to tolerate therapy and, as a consequence, result in a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…TNF. on the other hand, has been shown to induce diffuse alveolar damage with neerosis of alveolar epithelial and endothelial cells [37]. Thus, in the response to respirable mineral fibres, TNF will add a synergistic factor to the generation of reactive oxygen species by PMN.…”
Section: Discussionmentioning
confidence: 99%
“…Increased systemic TNF-a has been implicated as a mechanism of cachexia, skeletal muscle atrophy and weakness in COPD patients. Chronic administration of TNF-a in animals results in cachexia, anaemia, leukocytosis and infiltration of neutrophils into organs such as the heart, liver and spleen [17].…”
Section: Interleukin-6mentioning
confidence: 99%